PERAN TENTARA DALAM POLITIK ORDE BARU: STUDI KASUS SOEHARTO DAN ABRI - Tamba, Naomy Elisabeth; Simanjuntak, Jessica; Buulolo, Ayu Linsa; Surbakti, Sophia Rheina (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This study aims to analyze the role of the army in New Order politics in Indonesia, focusing on the policies and actions of President Suharto and the Armed Forces of the Republic of Indonesia (ABRI). The New Order was an important period in Indonesian history marked by military rule under General Suharto for more than three decades. This research uses historical research methods to explore historical records, government policies, and the role of ABRI in the formation and maintenance of New Order political power. Through an in-depth analysis of primary and secondary sources, this study attempts to answer several key questions, including how ABRI's role in maintaining political stability during the New Order, how the relationship between Suharto and ABRI influenced policymaking, and how this role influenced Indonesia's political, economic, and social development. The results showed that ABRI had a key role in maintaining the New Order regime by providing security support, supervising the political opposition, and being involved in key policymaking. The close relationship between Suharto and ABRI also established a strong power dynamic in Indonesia during this period. In addition, ABRI's role in managing social and political conflicts has an impact on the social and economic development of the country. This research provides in-depth insight into the role of the military in New Order politics and its relevance to political developments in Indonesia today. The political and social implications of ABRI's role in the New Order will also be discussed, as well as its impact on the democratic transition in Indonesia after the fall of the Suharto regime.